Study the Nexus between Indicators of Surface Water Quality on the Small River for Better Basin Management - MITRYASOVA, Olena; MATS, Andrii; SALAMON, Ivan; SMYRNOV, Victor; CHVYR, Vadym (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).03, 2023)
Purpose is determination of interdependencies between hydrochemical indicators of surface water quality in the example of a small river as a limiting factor of formation of aquatic ecosystem of territories. Correlation analyses of the studied indicators of water quality was conducted on an average value of each indicator (pH, phosphates, nitrates, BOD, COD, soluble oxygen). Found a significant increase in phosphates with time, with a coefficient of correlation R=0.71, indicating contamination of the water facility. This can be explained by the arrival of various surface-active substances and, to a lesser extent, the lack of quality sewage treatment facilities. Positive changes are founded in water object that is related to a decrease in the value of BOD. This is due to a decrease in the use of oxygen on oxidation of inorganic and organic substances. In general, the use of river runoff of the river above normal, and the overall environmental state of river basin is defined as "extremely poor".